2021
DOI: 10.1111/ijac.13941
|View full text |Cite
|
Sign up to set email alerts
|

Application of sputtered ceramic TiC/a:C thin films with different structures by changing the deposition parameters

Abstract: Titanium carbide-based thin films have been produced by DC magnetron sputtering. It was demonstrated that the same technology with changing of the deposition parameters, such as deposition temperature or power of Ti target, resulted in the preparation of TiC/a:C thin films with various structures. The structure of thin films and volume fraction of amorphous and crystal phases were precisely tailored by the control of deposition parameters. These ceramic nanocomposite TiC/a:C thin films according to their vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It should explicitly be mentioned that such materials, in the form of thin films and bulk materials, generally exhibit further interesting physical and chemical properties, making them suitable candidates, for example, for electrical [18,60] and optical applications [63,64,98], medical and biofunctional surfaces [20,59,99,100], electrochemical storage [101,102] and other applications [103]. The opportunity to tune and tailor properties, functionalities and microstructure of such materials will have a huge impact on future materials research, advanced synthesis and utilization, as has been demonstrated recently for magnetron-sputter-deposited TiC/a-C thin films [104][105][106].…”
Section: Introductionmentioning
confidence: 99%
“…It should explicitly be mentioned that such materials, in the form of thin films and bulk materials, generally exhibit further interesting physical and chemical properties, making them suitable candidates, for example, for electrical [18,60] and optical applications [63,64,98], medical and biofunctional surfaces [20,59,99,100], electrochemical storage [101,102] and other applications [103]. The opportunity to tune and tailor properties, functionalities and microstructure of such materials will have a huge impact on future materials research, advanced synthesis and utilization, as has been demonstrated recently for magnetron-sputter-deposited TiC/a-C thin films [104][105][106].…”
Section: Introductionmentioning
confidence: 99%